2021
DOI: 10.1111/jvp.12980
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics of a cytosine arabinoside subcutaneous protocol in dogs with meningoencephalomyelitis of unknown aetiology

Abstract: Cytosine arabinoside (CA) is a commonly used treatment for dogs with meningoencephalomyelitis of unknown aetiology (MUE) with various proposed protocols, many requiring 24 hours (h) of hospitalization or two visits within 24 h. This is a unidirectional study evaluating the pharmacokinetics of a CA subcutaneous (SC) protocol and a standard constant rate infusion (CRI) protocol in 8 dogs with MUE. Dogs received the CRI (200 mg/m2 IV over 24 h), followed by a SC protocol (50 mg/m2 every 2 h for 4 treatments) four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…When plasma concentrations of CA were compared between groups, the Cmax was greater in the SC group for the initial 8 hours of drug administration, but greater in the IV CRI group from 12 to 24 hours after treatment initiation. 19 Although the SC administration yielded a greater Cmax in that study, 19 the IV CRI maintained a more sustained peak plasma concentration. The mean plasma concentration of our study was greater than 1 μg/mL from 4 to 10 hours after initiation of the 8-hour infusion, which was longer than the maintenance of a similar plasma concentration in the SC bolus group in the study by Levitan et al 19 Although the mean plasma concentration in our study dropped to less than 1 μg/mL after 10 hours, it is likely that a longer infusion with the Omnipod device could also result in a prolonged steady-state concentration comparable to a 24-hour IV CRI.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…When plasma concentrations of CA were compared between groups, the Cmax was greater in the SC group for the initial 8 hours of drug administration, but greater in the IV CRI group from 12 to 24 hours after treatment initiation. 19 Although the SC administration yielded a greater Cmax in that study, 19 the IV CRI maintained a more sustained peak plasma concentration. The mean plasma concentration of our study was greater than 1 μg/mL from 4 to 10 hours after initiation of the 8-hour infusion, which was longer than the maintenance of a similar plasma concentration in the SC bolus group in the study by Levitan et al 19 Although the mean plasma concentration in our study dropped to less than 1 μg/mL after 10 hours, it is likely that a longer infusion with the Omnipod device could also result in a prolonged steady-state concentration comparable to a 24-hour IV CRI.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, in that study, the mean total AUC from IV CRI was 22.58 μg X hour/mL (SD, 3.19 μg X h/mL). Levitin et al 19 administered CA as an IV CRI in dogs with MUE at a rate of 8.33 mg/m 2 /hour over 24 hours (total dose, 200 mg/m 2 ), which produced a Cmax and AUC of 1.09 μg/mL and 15.74 μg X hour/ mL, respectively. They did not calculate Tmax in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, there is also the question of whether the administered dose of cytarabine was sufficiently high to achieve therapeutically useful blood levels. This specific issue has been examined in many recent publications but, specifically, it was shown that 200 mg/m 2 [double the dose used in ( 55 )] CRI cytarabine over 24 h was unreliable at producing durable blood levels above 1μg/mL (the presumed therapeutic level) ( 64 ). Nevertheless, whether the efficacy of cytarabine is time- (above threshold) or concentration-dependent is still not established.…”
Section: Updates Of Outcomes Associated With Specific Medicationsmentioning
confidence: 99%
“…In the article by Levitin HA, (2021), Hilary A. Levitin is listed as the corresponding author in the published version.…”
mentioning
confidence: 99%